Pembelajaran Berbasis Proyek Mind Mapping Dengan Aplikasi Canva Pada Mata Pelajaran PPKN Di SD - Dewi Wulandari; Sutrisna Wibawa (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to determine significant differences in Civics learning outcomes between groups of students who took part in mind mapping project-based learning with the Canva application and groups of students who took part in conventional learning in class V. The research design used a quasi-experimental design. The research sample was taken using a simple random sampling technique so that 15 class V students were selected as the experimental class and 15 students as the control class. Data collection uses observation and PPKn learning outcomes tests. Data analysis techniques use descriptive statistics and inferential statistics, where inferential statistics are divided into three, namely normality tests, homogeneity tests, and hypothesis tests. The results of the research show that: 1) there are differences in Civics learning outcomes between students who take part in mind mapping project-based learning with the Canva application and students who take conventional learning, and 2) there is an influence of mind mapping project-based learning with the Canva application on learning outcomes in subjects PPK for fifth grade students at Ngringin State Elementary School